2011
DOI: 10.1038/pr.2011.754
|View full text |Cite
|
Sign up to set email alerts
|

Neonatal Ventilation: Evidence Based or Technological Conundrum

Abstract: Background: Meta analyses on neonatal mechanical ventilation suggested no difference between conventional and patient triggered ventilation (PTV) in preterm neonates. Newer forms of respiratory support with perceived advantages continue to entice Neonatologists. Objective: To ascertain the current trends in respiratory management of the very preterm infant (< 28 weeks) in level 3 neonatal units. Methods: A structured questionnaire was designed and a senior staff interviewed in all level 3 neonatal units in Eng… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Thus, it could have been expected that the adaptation of the brain to these biochemical changes had improved with time. Brain background activity is dependent on GA [14,15]; therefore, it is interesting that the effect of pCO 2 and glucose was similar in the two groups. Whether the effect on tABP caused by increased pCO 2 and blood glucose is a sign of a deleterious effect on the brain remains unclear.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, it could have been expected that the adaptation of the brain to these biochemical changes had improved with time. Brain background activity is dependent on GA [14,15]; therefore, it is interesting that the effect of pCO 2 and glucose was similar in the two groups. Whether the effect on tABP caused by increased pCO 2 and blood glucose is a sign of a deleterious effect on the brain remains unclear.…”
Section: Discussionmentioning
confidence: 99%
“…If a unit is only able to deliver special care, transfer may be necessary to a higher level unit and the type of ventilation may then be determined by unit practices and trends of use of various modes. A UK wide survey of ventilation strategies within 54 tertiary level neonatal units was undertaken (46) and found that the use and availability of modes to be variable. 98% response to a structured questionnaire found that pressure controlled ventilation was most frequently used as the primary form of ventilator support (69.8%) compared to volume targeted (24.5%) and HFOV (5.7%).…”
Section: Selecting or Switching Modes Of Ventilationmentioning
confidence: 99%